L-amino acid oxidase from Bothrops marajoensis causes nephrotoxicity in isolated perfused kidney and cytotoxicity in MDCK renal cells. (15th September 2015) - Dantas, Rodrigo Tavares; Jorge, Antônio Rafael Coelho; Jorge, Roberta Jeane Bezerra; Menezes, Ramon Róseo Paula Pessoa Bezerra de; Lima, Danya Bandeira; Torres, Alba Fabíola Costa; Toyama, Marcos Hikari; Monteiro, Helena Serra Azul; Martins, Alice Maria Costa
Abstract: Renal alterations caused by Bothrops venom and its compounds are studied to understand these effects and provide the best treatment. Previously, we studied the renal effect of the whole venom of Bothrops marajoensis and its phospholipase A2 (PLA2 ), but these effects could not to be attributed to PLA2. To continue the study, we report in this short communication the effects ofl -amino acid oxidase from B. marajoensis venom (LAAOBm) on renal function parameter alterations observed in the same model of isolated perfused kidney, as well as the cytotoxic effect on renal cells. LAAOBm caused a decrease in PP, RVR, UF, GFR, %TNa + and %TCl −, very similar to the effects of whole venom using the same model. We also demonstrated its cytotoxicity in MDCK cells with IC50 of 2.5 μg/mL and late apoptotic involvement demonstrated by flow cytometry assays. In conclusion, we suggested that LAAOBm is a nephrotoxic compound of B. marajoensis venom. Highlights: LAAO from Bothrops marajoensis (LAAOBm) venom alters renal function parameters. LAAOBm is cytotoxicity on epithelial distal tubular MDCK renal cells. Apoptotic mechanism is involved on LAAOBm in vitro cytotoxicity.